Oral Ulcers as an Initial Presentation of Juvenile Pemphigus: A Case Report - I-Hsuan Chen; Shu-Chi Mu; Dino Tsai; Yuh-Yu Chou; Li-Fang Wang; Ling-Jen Wang (Elsevier, 2016)
Pemphigus vulgaris (PV) is an autoimmune disease in which the autoantibody, immunoglobulin G, is directed against the keratinocytes in the epidermis. The classic presentations of PV are flaccid vesicles or bullae over the oral mucosa, trunk, groin, and extremities. The age of onset is usually between 40 and 60 years, and cases of PV in children or adolescent patients are rare. Here, we present a 17-year-old boy who had painful oral ulcers for 3 months initially and bullae spreading to the whole body in the following days. Paraneoplastic pemphigus was another differential diagnosis due to the atypical appearance of the skin lesion. However, PV was confirmed by hematoxylin and eosin staining and immunofluorescence examination of the skin biopsy specimens. The patient had a good response to corticosteroid treatment and the immunosuppressive agent, rituximab.